Online Digital Applications for Managing AudioVisual Teaching Resources: the Model of Labcom UJI - Arnau Roselló, Roberto; Martín Núñez, Marta (Estudios sobre el Mensaje Periodístico, 2013)
The immersion of practical content in the new European Space for Higher Education is causing a transformation of the model in the management of teaching laboratories, whose primary aim is to support undergraduate and posgraduate teaching. The development of a collaborative working tool based on an interactive web application, which serves the three types of users of a laboratory of its kind (teaching staff, administration staff and students), involves designing templates, workflows and interfaces that make a real improvement of the processes. In this paper we try to approach the process of design, development and implementation of the application LABGEST from the idea to the final product, developed at the Laboratory of Communication Sciences at the Universitat Jaume I of Castellón.